Jalan Terbaikku Adalah Bercerai Denganmu - Very Julianto; Nadhifah D. Cahyani (UIN Sunan Kalijaga, 2017)
A divorce experienced by a person often has a negative impact on the couple experiencing it, as well as the family involved. But not a few divorce that actually brings happiness to those who experience it. Surely this happens through a certain process. This study seeks to reveal the happiness felt by someone who has experienced divorce. This study is a case study conducted on four subjects who filed a divorce suit. The results of interviews and observations on the four subjects showed that the four subjects were happy after divorcing from their former partner. This study shows that in certain marriage cases divorce is the last solution that can be taken because of certain issues such as differences in partner's vision and mission, infidelity, inappropriate marital roles and household economic problems. This suggests that if a marriage forced to persist actually creates problems for couples and families within it, then divorce can be the best way by prior consideration and special preparation.